Submicrosecond electron accelerator based on pulsed transformer; Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment; Vol. 969 - Poloskov A. V. Artem Viktorovich; Egorov I. S. Ivan Sergeevich; Nashilevsky A. V. Aleksandr Vladimirovich; Ezhov V. V. Vitali Vladimirovich; Smolyanskiy (Smolyansky, Smolyanskii) E. A. Egor Aleksandrovich; Serebrennikov M. A. Maksim Anatolevich; Remnev (Remnyov) G. E. Gennady Efimovich (2020, 2020)
Title screen